Life-Threatening Event Risk in Children With Wolff-Parkinson-White Syndrome: A Multicenter International Study - Etheridge, Susan P; Escudero, Carolina A; Blaufox, Andrew D; Law, Ian H; Dechert-Crooks, Brynn E; Stephenson, Elizabeth A; Dubin, Anne M; Ceresnak, Scott R; Motonaga, Kara S; Skinner, Jonathan R; Marcondes, Luciana D; Perry, James C; et al. (JACC. Clinical electrophysiology, 2018)
OBJECTIVES: This study sought to characterize risk in children with Wolff-Parkinson-White (WPW) syndrome by comparing those who had experienced a life-threatening event (LTE) with a control population. BACKGROUND: Children with WPW syndrome are at risk of sudden death. METHODS: This retrospective multicenter pediatric study identified 912 subjects ≤21 years of age with WPW syndrome, using electrophysiology (EPS) studies. Case subjects had a history of LTE: sudden death, aborted sudden death, or atrial fibrillation (shortest pre-excited RR interval in atrial fibrillation [SPERRI] of ≤250 ms or with hemodynamic compromise); whereas subjects did not. We compared clinical and EPS data between cases and subjects. RESULTS: Case subjects (n = 96) were older and less likely than subjects (n = 816) to have symptoms or documented tachycardia. Mean age at LTE was 14.1 ± 3.9 years of age. The LTE was the sentinel symptom in 65%, consisting of rapidly conducted pre-excited atrial fibrillation (49%), aborted sudden death (45%), and sudden death (6%). Three risk components were considered at EPS: SPERRI, accessory pathway effective refractory period (APERP), and shortest paced cycle length with pre-excitation during atrial pacing (SPPCL), and all were shorter in cases than in control subjects. In multivariate analysis, risk factors for LTE included male sex, Ebstein malformation, rapid anterograde conduction (APERP, SPERRI, or SPPCL ≤250 ms), multiple pathways, and inducible atrial fibrillation. Of case subjects, 60 of 86 (69%) had ≥2 EPS risk stratification components performed; 22 of 60 (37%) did not have EPS-determined high-risk characteristics, and 15 of 60 (25%) had neither concerning pathway characteristics nor inducible atrioventricular reciprocating tachycardia. CONCLUSIONS: Young patients may experience LTE from WPW syndrome without prior symptoms or markers of high-risk on EPS.
Keywords: Death, Sudden; dítě; Atrial Fibrillation; náhlá smrt; Adolescent; Retrospective Studies; fibrilace síní; lidé; Risk Factors; Wolff-Parkinson-White syndrome; Female; Wolffův-Parkinsonův-Whiteův syndrom; Male; pediatrics; ženské pohlaví; sudden death; Humans; Child; mužské pohlaví; rizikové faktory; Wolff-Parkinson-White Syndrome; mladiství; retrospektivní studie